The Importance of Having Self Disclosure in Lesbians - Robbi Asri; Afdal Afdal (Jurnal Neo Konseling, 2020)
Ideally, humans have sexual desires towards the opposite sex, but what is happening now, there are still many who are not operating in accordance with the norms and cultures in society, someone has deviant behavior, for example lesbians. Currently many cases of lesbians are found in the community, not a few of the lesbians choose to try to be open to parents and demand acceptance. However, on the other hand there are still many lesbians who choose to hide their sexual identities from their parents for various reasons. This study aims to look at the ability of self disclosure possessed by lesbians in their parents. This type of research is a qualitative research in the form of case studies. Subjects in this study amounted to two students using Purposive Sampling (Purposive Sampling) techniques. Data collection instruments used in this study were interview, observation, and documentation guidelines. Analysis of the data in this study through three stages, namely (1) data reduction; (2) data exposure (data display); (3) conclusion drawing and verification (conclusion drawing / verifying). The data analysis technique used in this study was thematic analysis by verifying the interview transcript. The study was assisted by an automatic recording device in the form of a smartphone. The results revealed that all research subjects (lesbians) had low self disclosure, both the amount, valence, accuracy, intention, and intimacy to their parents. Therefore this research is expected to help lesbians increase their openness, and help prevent lesbians from developing by asking for cooperation from various parties.